Fish oil supplementation with various lipid emulsions suppresses in vitro cytokine release in home parenteral nutrition patients: a crossover study - Novak, Frantisek; Vecka, Marek; Meisnerova, Eva; Sevela, Stanislav; Vavrova, Lucie; Rychlikova, Jana; Dolezalova, Ludmila; Myslivcova, Denisa; Zak, Ales; Vitek, Libor; Novakova, Olga (Nutrition research, 2019)
Long-chain n-3 polyunsaturated fatty acids modulate immune cell functions. The primary objective of this study was to evaluate the impact of different lipid emulsions (LEs) with supplemented doses of fish oil (FO) on serum cytokine concentration and in vitro cytokine production in patients with intestinal failure on home parenteral nutrition (HPNPs). We hypothesized that FO supplementation would diminish lipopolysaccharide (LPS)-stimulated cytokine production. Twelve HPNPs receiving Smoflipid for at least 3 months were given FO (Omegaven) for a further 4 weeks. After this cycle, the patients were randomized to subsequently receive 1 cycle with Lipoplus and 1 cycle with ClinOleic for 6 weeks or vice versa plus 4 weeks of added Omegaven after each cycle in a crossover design. Comparison of the baseline LE regimens showed lower LPS-stimulated production of IL-1β in the HPNPs on Lipoplus than on the Smoflipid and ClinOleic regimens, as well as lower IL-8 compared to the Smoflipid regimen. Omegaven reduced IL-8 concentration in serum under the Lipoplus regimen and diminished LPS-stimulated production of IL-1β under the Smoflipid and ClinOleic. IL-6 and TNF-α production was depressed only in those on Smoflipid. Irrespective of the LE used, the HPNPs compared to the healthy controls showed higher IL-6, IL-8, and TNF-α concentrations in serum and LPS-stimulated production of IL-6 as well as lower n-6/n-3 long-chain polyunsaturated fatty acids in the erythrocyte phospholipids. LPS-stimulated production of IL-6 correlated negatively with the parenteral dose of eicosapentaenoic acid + docosahexaenoic acid. In conclusion, FO-supplemented parenteral nutrition suppresses in vitro cytokine production.
Keywords: dospělí; Female; klinické křížové studie; Cytokines; Fat Emulsions, Intravenous; Adult; ženské pohlaví; In Vitro Techniques; Dietary Supplements; Fish Oils; tukové emulze intravenózní; cytokiny; techniky in vitro; lidé; potravní doplňky; Aged, 80 and over; Cross-Over Studies; parenterální výživa doma; Male; Aged; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Parenteral Nutrition, Home; rybí oleje; Middle Aged; Humans